Sex differences in cognitive functioning of patients at-risk for psychosis and healthy controls: Results from the European Gene–Environment Interactions study. Issue 1 (2020) - Menghini-Müller, Stephanie; Studerus, Erich; Ittig, Sarah; Valmaggia, Lucia R.; Kempton, Matthew J.; van der Gaag, Mark; de Haan, Lieuwe; Nelson, Barnaby; Bressan, Rodrigo A.; Barrantes-Vidal, Neus; Jantac, Célia; Nordentoft, Merete; et al.
Abstract: Background: Sex differences in cognitive functioning have long been recognized in schizophrenia patients and healthy controls (HC). However, few studies have focused on patients with an at-risk mental state (ARMS) for psychosis. Thus, the aim of the present study was to investigate sex differences in neurocognitive performance in ARMS patients compared with HC. Methods: The data analyzed in this study were collected within the multicenter European Gene–Environment Interactions study (11 centers). A total of 343 ARMS patients (158 women) and 67 HC subjects (33 women) were included. All participants completed a comprehensive neurocognitive battery. Linear mixed effects models were used to explore whether sex differences in cognitive functioning were present in the total group (main effect of sex) and whether sex differences were different for HC and ARMS (interaction between sex and group). Results: Women performed better in social cognition, speed of processing, and verbal learning than men regardless of whether they were ARMS or HC. However, only differences in speed of processing and verbal learning remained significant after correction for multiple testing. Additionally, ARMS patients displayed alterations in attention, current IQ, speed of processing, verbal learning, and working memory compared with HC. Conclusions: Findings indicate that sex differences in cognitive functioning in ARMS are similar to those seen between healthy men and women. Thus, it appears that sex differences in cognitive performance may not be specific for ARMS, a finding resembling that in patients with schizophrenic psychoses.